Histopathological diagnosis of surgical speciments in a Tertiary Hospital in Dhaka - Rahman, Md Tahminur; Shirin, Sonia; Sarnali, Tanjila Tahmin; Mumu, Mahbuba Ashrafi (Bangladesh Journal of Pathology, 2010)
Key words: Surgically resected specimen; histopathological diagnosis and its importance DOI: 10.3329/bjpath.v24i2.4111 Bangladesh J Pathol 24(2): 8-10